Selection of Optimal Bending Types in Die Process of L-Shaped Panels Considering the Springback Behaviours (International Journal of Engineering Materials and Manufacture, 2024)
In die designing, one of the most crucial decisions is selecting the appropriate die process required to produce panels. The challenge for die designer is to comprehend the behaviour of the panel material in relation to the die processes. If the die process is not correctly determined before die fabrication, severe panel spring back may occur, which can become difficult and require additional time and effort to rectify. This paper presents research aimed at understanding the behaviour of different types of bending process combinations concerning the spring back occurrence during the stamping process of an L-shaped design intent panel. Using simulation and experiment, three types of materials with different tensile properties of 270 MPa, 440 MPa and 590 MPa, but the same thickness of 1.8 mm, were selected. The results were compared, analysed and optimized by using Response Surface Methodology (RSM) method. The results demonstrate that one-process bending with full bending (compress type) approach, is the most suitable for the three materials type L-shaped panel. The study provides guidelines for die design engineers, industrial practitioners and researchers to decide on the best approach for die process decisions, when dealing with specific panels properties, shape and thickness.